2011
DOI: 10.1016/j.metabol.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone resorption and impaired bone microarchitecture in short-term and extended high-fat diet–induced obesity

Abstract: Although obesity traditionally has been considered a condition of low risk for osteoporosis, this classic view has recently been questioned. The aim of this study was to assess bone microarchitecture and turnover in a mouse model of high-fat diet-induced obesity. Seven-week-old male C57BL/6J mice (n = 18) were randomized into 3 diet groups. One third (n = 6) received a low-fat diet for 24 weeks, one third was kept on an extended high-fat diet (eHF), and the remaining was switched from low-fat to high-fat chow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
131
5
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 51 publications
20
131
5
6
Order By: Relevance
“…The mechanism causing larger holes in the trabecular bone network at the radius in participants with type 2 DM is not fully understood. However, studies in rodent models of type 2 DM and in rodents fed high-fat diets have demonstrated a reduction in osteoblast recruitment and mineral apposition rate and an increase in osteoclastogenesis, resulting in an imbalance between bone formation and resorption (42,43). Cross-sectional findings in humans further support these data, as serum markers of bone formation, such as osteocalcin, are lower and markers of bone resorption, such as C-terminal telopeptide of type 1 collagen, are elevated in participants with type 2 DM (44,45).…”
Section: Pritchard Et Almentioning
confidence: 99%
“…The mechanism causing larger holes in the trabecular bone network at the radius in participants with type 2 DM is not fully understood. However, studies in rodent models of type 2 DM and in rodents fed high-fat diets have demonstrated a reduction in osteoblast recruitment and mineral apposition rate and an increase in osteoclastogenesis, resulting in an imbalance between bone formation and resorption (42,43). Cross-sectional findings in humans further support these data, as serum markers of bone formation, such as osteocalcin, are lower and markers of bone resorption, such as C-terminal telopeptide of type 1 collagen, are elevated in participants with type 2 DM (44,45).…”
Section: Pritchard Et Almentioning
confidence: 99%
“…This weight gain, seen in both young and aging mice, is associated with visceral adiposity, insulin resistance, and, in some instances, bone loss. (62,63) But other studies have shown that C57BL/6 mice on an HFD have higher marrow adipose tissue yet either normal or increased aBMD. (64,65) Moreover, rates of bone formation in mice fed an HFD are either normal (64) or are temporally increased followed by a significant decrease in bone turnover concurrent with development of obesity and glucose intolerance.…”
Section: Skeletal Control Of Metabolic Balancementioning
confidence: 99%
“…Impaired glucose tolerance is more severe in males than females [33]. The C57BL/6J mouse appears to have adverse effects on trabecular bone components [34], and recent evidence suggests that the effect of the high-fat diet is more pronounced in skeletally immature compared to skeletally mature mice [35][36][37]. Lower trabecular bone volumes are primary the result of increased osteoclast resorption as indicated by serum biomarkers and histomorphotometry [35][36][37], though bone formation is also decreased [38].…”
Section: Bone Loss In Obese Type 2 Diabetesmentioning
confidence: 99%
“…The C57BL/6J mouse appears to have adverse effects on trabecular bone components [34], and recent evidence suggests that the effect of the high-fat diet is more pronounced in skeletally immature compared to skeletally mature mice [35][36][37]. Lower trabecular bone volumes are primary the result of increased osteoclast resorption as indicated by serum biomarkers and histomorphotometry [35][36][37], though bone formation is also decreased [38]. Interestingly, recent data indicate that whereas body weight and fasting glucose levels can return to normal after a return to a normal diet, trabecular bone loss prior to skeletal maturity may not be recoverable without some other types of intervention [34].…”
Section: Bone Loss In Obese Type 2 Diabetesmentioning
confidence: 99%